2014
DOI: 10.1590/0103-6440201302382
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Activity of an Experimental Dentifrice Based on Ricinus Communis

Abstract: This study evaluated the antimicrobial activity of a Ricinus communis-based experimental dentifrice for denture hygiene against the following standard strains: Staphylococcus aureus, Escherichia coli, Streptococcus mutans, Enterococcus faecalis, Candida albicans and Candida glabrata. The minimum inhibitory concentration (MIC) assay was performed with R. communis in pure oil at 2.5%. Only E. coli was not inhibited by R. communis, but the MIC (0.0781%) was effective against the other microorganisms. From these r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 20 publications
3
33
0
19
Order By: Relevance
“…In addition, it is also biocompatible 9 and has detergent properties. There are studies evaluating the efficiency of R. communis solution in achieving complete denture hygiene, although experimental designs are diverse and results are inconclusive 2 , 10 , 19 , 20 , 22 , 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is also biocompatible 9 and has detergent properties. There are studies evaluating the efficiency of R. communis solution in achieving complete denture hygiene, although experimental designs are diverse and results are inconclusive 2 , 10 , 19 , 20 , 22 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Since most of the current methods used for denture hygiene do not present all these characteristics, numerous studies have been conducted in an attempt to find an optimal protocol 2 , 4 , 7 , 10 , 16 , 19 , 20 , 22 - 24 , 26 , 27 , 29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the prevalence of different Candida species is significantly higher in denture wearers and that Candida albicans is frequently implicated in denture stomatitis (DS), inflammation of the mucosa underlying a complete denture . Denture cleansers containing Ricinus communis are in development with different formulations and concentrations . In a preliminary study, Leite et al evaluated the antimicrobial activity of an R. communis ‐based experimental dentifrice for denture hygiene and demonstrated that the R. communis dentifrice at 10% caused the largest zones of bacterial growth inhibition and that it had similar antimicrobial activity to the commercial dentifrices, except against S. aureus .…”
mentioning
confidence: 99%
“…15 Denture cleansers containing Ricinus communis are in development with different formulations and concentrations. 6,[16][17][18][19] In a preliminary study, Leite et al 17 evaluated the antimicrobial activity of an R. communis-based experimental dentifrice for denture hygiene and demonstrated that the R. communis dentifrice at 10% caused the largest zones of bacterial growth inhibition and that it had similar antimicrobial activity to the commercial dentifrices, except against S. aureus. Roselino et al 20 concluded that the same formulation of the experimental R. communis dentifrice did not cause surface roughness and color alteration in artificial teeth.…”
mentioning
confidence: 99%